Adjunctive moxifloxacin in the treatment of generalized aggressive periodontitis patients: clinical and microbiological results of a randomized, triple-blind and placebo-controlled clinical trial - Ardila, Carlos Martín; Martelo-Cadavid, Juan Felipe; Boderth-Acosta, Gina; Ariza-Garcés, Astrid Adriana; Guzmán, Isabel C. (Journal of clinical periodontology, 2015)
Aim The aim of the present study was to evaluate the clinical and microbiological efficacy of moxifloxacin (MOX) in one‐stage scaling and root planing (SRP) in treating generalized aggressive periodontitis (GAgP). Materials and Methods Forty subjects were randomly allocated to two treatment groups. The two treatment groups consisted of SRP combined with systemically admi‐nistered MOX at the dosage of 400 mg once daily for 7 days or SRP + placebo once daily for 7 days. Subgingival plaque samples were analysed for cultivable bacteria. Results Both groups resulted in significant reduction of probing depth (PD) and clinical attachment level (CAL) compared with baseline (p < 0.0001), and this difference was maintained at 6 months from baseline in both groups. However, subjects receiving MOX showed the greatest improvements CAL, and PD. Subjects in both groups at 6 months displayed the greatest reduction from baseline in frequency of sites with PD ≥6 mm (p < 0.001), favouring the MOX group. Adjunctive antibiotic protocol reduced subgingival Aggregatibacter actinomycetemcomitans to undetectable levels, after 3 and 6 months, and there was a significant reduction in the levels of Porphyromonas gingivalis and Tannerella forsythia in the MOX group compared to the placebo group. Conclusions The results from this study suggest that moxifloxacin as and adjunct to one‐stage full‐mouth SRP leads to a better clinical and microbiological advantages compared to mechanical treatment.